Analysis of the Polypropylene-Based Aluminium-Air Battery - Tan, Weng Cheong; Saw, Lip Huat; Yew, Ming Chian; Sun, Dongyang; Cai, Zuansi; Chong, Wen Tong; Kuo, Pei-Yu (Frontiers in Energy Research, 2021)
Global energy demand is rising due to the rapid development and adoption of new technologies in every sector. Hence, there is a need to introduce a clean energy source that does not cause damage to the environment. Aluminium-air battery with its high theoretical specific volumetric capacity is an exciting alternative for post-lithium energy storage and has been at the forefront of energy research for years. However, the conventional aqueous electrolyte-based aluminium-air battery with bulky liquid storage, parasitic corrosion of aluminium in contact with the electrolyte, and formation of a passive oxide or hydroxide layer has precluded its widespread application. In order to achieve successful simplification and cost-effectiveness, a novel idea of a polypropylene-based aluminium-air battery is proposed. In this work, a polypropylene-based aluminium-air battery was constructed using aluminium foil as an anode, carbon fiber cloth as an air-cathode, and Polypropylene and Kimwipes as the separator. The effects of the electrolyte concentration on the aluminium-air battery were investigated and analyzed using various discharge currents. The study showed that the performance of the polypropylene separator is better than that of the Kimwipes separator. The battery capacity is negatively correlated with the concentrations of the electrolyte. At a discharge current of 30 mA, the aluminium-air battery has a specific capacity of 375 mAh g−1 when 1 M of potassium hydroxide was used as electrolyte.